SLCO1B1 rs4149056 polymorphism associated with statin-induced myopathy is differently distributed according to ethnicity in the Brazilian general population: Amerindians as a high risk ethnic group - Krieger José E; Mill José G; Machado-Coelho George LL; Nascimento Raimundo M; Soares Renata AG; Santos Paulo CJL; Pereira Alexandre C (BMC, 2011)
Abstract Background Recent studies reported the association between SLCO1B1 polymorphisms and the development of statin-induced myopathy. In the scenario of the Brazilian population, being one of the most heterogeneous in the world, the main aim here was to evaluate SLCO1B1 polymorphisms according to ethnic groups as an initial step for future pharmacogenetic studies. Methods One hundred and eighty-two Amerindians plus 1,032 subjects from the general urban population were included. Genotypes for the SLCO1B1 rs4149056 (c.T521C, p.V174A, exon 5) and SLCO1B1 rs4363657 (g.T89595C, intron 11) polymorphisms were detected by polymerase chain reaction followed by high resolution melting analysis with the Rotor Gene 6000® instrument. Results The frequencies of the SLCO1B1 rs4149056 and rs4363657 C variant allele were higher in Amerindians (28.3% and 26.1%) and were lower in African descent subjects (5.7% and 10.8%) compared with Mulatto (14.9% and 18.2%) and Caucasian descent (14.8% and 15.4%) ethnic groups (p < 0.001 and p < 0.001, respectively). Linkage disequilibrium analysis show that these variant alleles are in different linkage disequilibrium patterns depending on the ethnic origin. Conclusion Our findings indicate interethnic differences for the SLCO1B1 rs4149056 C risk allele frequency among Brazilians. These data will be useful in the development of effective programs for stratifying individuals regarding adherence, efficacy and choice of statin-type.